Erythrocyte–Platelet Interaction in Uncomplicated Pregnancy. (3rd December 2014) - Swanepoel, Albe C.; Pretorius, Etheresia
Abstract Maternal and fetal requirements during uncomplicated pregnancy are associated with changes in the hematopoietic system. Platelets and erythrocytes [red blood cells (RBCs)], and especially their membranes, are involved in coagulation, and their interactions may provide reasons for the changed hematopoietic system during uncomplicated pregnancy. We review literature regarding RBC and platelet membrane structure and interactions during hypercoagulability and hormonal changes. We then study interactions between RBCs and platelets in uncomplicated pregnancy, as their interactions may be one of the reasons for increased hypercoagulability during uncomplicated pregnancy. Scanning electron microscopy was used to study whole blood smears from 90 pregnant females in different phases of pregnancy. Pregnancy-specific interaction was seen between RBCs and platelets. Typically, one or more platelets interacted through platelet spreading and pseudopodia formation with a single RBC. However, multiple interactions with RBCs were also shown for a single platelet. Specific RBC–platelet interaction seen during uncomplicated pregnancy may be caused by increased estrogen and/or increased fibrinogen concentrations. This interaction may contribute to the hypercoagulable state associated with healthy and uncomplicated pregnancy and may also play a fundamental role in gestational thrombocytopenia.